Аналіз течій узагальнених ньютонівських рідин вздовж профільованих поверхонь - Желяк, В.; Кончевич, Я. (Видавництво Національного університету “Львівська політехніка”, 2004)
In activity the review of researches on flow of generalized Newtonian liquids on an inclined contoured surface is shown. Is rotined, that the problems of pressure head two-layer flows in a flat channel are unsufficiently probed.
Keywords: 532.516